METODE BELAJAR MEMBACA TANPA MENGEJA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA ANAK USIA DINI PADA BIMBINGAN BELAJAR ANAK HEBAT (AHE) DIMASA PANDEMI - Nur Amalafitra; Sholihatul Muawanah; Budi Sasomo (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study was to find out the method of reading without spelling can improve children's reading skills at the Great Children's Tutoring (AHE) unit Kersoharjo, Geneng District, Ngawi Regency. This research uses descriptive qualitative research. The place of this research is AHE tutoring in Kersoharjo village, Geneng sub-district, Ngawi district. Research informants are tutors, students, and guardians of students in AHE tutoring. The data were collected using observation and interview techniques. To test the validity of the data, triangulation technique was used. The data that has been collected was analyzed using an interactive model. The results showed that: the process of applying the method of learning to read without spelling to improve reading skills in children in AHE tutoring, went through several stages as follows: 1) conditioning the child by telling the child to sit down and preparing writing instruments, and doing brain exercises by drawing as desired. . this stage is in the preliminary activity, 2) invites children to read the module according to the level, 3) then invites children to write what they have got before, 4) invites children to play with letter card media. in stages 2 to 4 are included in the core activities, and continued in the closing activities. In the closing activity there is a stage of reviewing the material learned during one meeting